2014
DOI: 10.1021/nl503518q
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Electrochemical Transistor Utilizing a Nickel-Pyridyl Spinterface

Abstract: Using a scanning tunnelling microscope break-junction technique, we produce 4,4'-bipyridine (44BP) single-molecule junctions with Ni and Au contacts. Electrochemical control is used to prevent Ni oxidation, and to modulate the conductance of the devices via non-redox gating -the first time this has been shown using non-Au contacts. Remarkably the conductance and gain of the resulting Ni-44BP-Ni electrochemical transistors is significantly higher than analogous Au-based devices. Ab-initio calculations reveal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
84
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 34 publications
1
84
0
Order By: Relevance
“…Additional details on the instrument used in this study and the data acquisition/analysis process can be found in our previous publications. 43,44…”
Section: Scanning Tunnelling Microscopy Break Junction Measurementsmentioning
confidence: 99%
“…Additional details on the instrument used in this study and the data acquisition/analysis process can be found in our previous publications. 43,44…”
Section: Scanning Tunnelling Microscopy Break Junction Measurementsmentioning
confidence: 99%
“…Since the quantum interference in the charge transport through single-molecule junctions is energy dependent, the continuous tuning of the electrode potential offers an ideal strategy for realizing interference-based single-molecule electrochemical transistors (ECTs) [16][17][18][19][20][21][22] , and the high gating efficiency and relatively large gate voltage windows provide opportunities for gating single-molecule junctions between resonances associated with molecular energy levels and anti-resonances associated with DQI 18,23 .…”
mentioning
confidence: 99%
“…7,25 We plotted the molecular plateau length as a function of the number of benzene and methylene for the both cases with (blue) and without (red) the oxygen junction formation. The molecular plateau lengths were determined from the 2D conductance− displacement histograms of over 5000 traces for each profile.…”
Section: ■ Results and Discussionmentioning
confidence: 99%